Bank organization and loan contracting in small business financing - Andrea Bellucci; Alexander Borisov; Alberto Zazzaro (Institut für Angewandte Wirtschaftsforschung (IAW), 2016)
Academic research recognizes that the organizational structure of banks could have implications for the financing of small businesses and entrepreneurial firms. In this chapter, we start by reviewing the underlying theoretical motivation and then summarize existing evidence. Overall, it is confirmed that the organization of lending institutions is important for the use and transmission of information, as well as credit availability for small businesses. Moreover, using a unique dataset of bank loans, we empirically document that loan contract characteristics such as interest rates and collateral requirements are sensitive to the hierarchical allocation of decision-making authority within the bank's organization.
Keywords: 330; Bank organization structure; Authority allocation; Small business financing